Analisis Tingkat Laju Infiltrasi Pada Sub Daerah Aliran Sungai (DAS) Kampar Outlet Rimbo Panjang - Septria Dwi Hawari; Siswanto Siswanto; Trimaijon Trimaijon (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Infiltration is the process of entry of rainfall or surface water into the soil (subsurface) through the gap or pore space of the soil. The infiltration process is a very important part of the hydrological cycle which greatly affects the amount of water that is on the surface of the soil. In the area Rimbo Panjang-Pekanbaru has experienced changes in land use due to infrastructure development. Infiltration on each land use varies if the nature or type of soil is different. The instrument used to measure infiltration in the field is the double ring infiltrometer and the analytical method use the Horton method. Procedures for measuring infiltration rates in the field using SNI 7752:2012. Data obtained from the field in the form initial infiltration rate and constant infiltration rate. The results of the actual reduction data obtained the largest decrease of 7,2 cm and the smallest decrease of 0,1 cm. The largest initial infiltration capacity is 165 cm/hours and the smallest initial infiltration capacity is 3 cm/hours. The largest infiltration rate 152 cm/hours and the smallest infiltration rate 2,68 cm/hours. In the Rimbo Panjang-Pekanbaru area, the infiltration rate is in the slow, moderate and very fast class with the highest total volume value of 708,81 mm in the 2,75 hours and the smallest total infiltration volume valume 9,93 mm in 1 hour. Keywords: Infiltration, Horton Method, Subsurface Runoff